Identification of a proximal promoter region critical for the expression of the beta-F1-ATPase gene during Drosophila melanogaster development. - Ugalde, C.; Ochoa, P.; Perez, M.L.; Fernandez-Moreno, M.A.; Calleja, M.; Alahari, A.; Kaguni, L.S.; Garesse, R. (Mitochondrion, 2001)
We have studied the spatio-temporal pattern of expression of the gene encoding the H(+) adenosine triphosphate (ATP) synthase beta subunit (beta-F1-ATPase) during Drosophila melanogaster development. The beta-F1-ATPase mRNA is stored in the egg; as development proceeds it is distributed in most embryonic cellular territories, including the mesoderm, and in late embryos it is highly abundant in the ventral cord and midgut. Using a combination of transfection assays in Schneider cells and P-element transformation in flies, we have identified a proximal 5' upstream region of 258 bp essential for the transcriptional activity of the gene during D. melanogaster embryogenesis that is virtually inactive in adult tissues. Electrophoretic mobility shift assays using specific DNA fragments from the 258-bp region detect in embryonic nuclear extracts a complex set of DNA binding proteins that are largely absent in adults. The transcription factor CF2-II has been identified as a potential candidate in the regulation of the beta-F1-ATPase gene.